Book Review: In the Shadow of the Palms: More-Than-Human Becomings in West Papua. Sophie Chao. Duke University Press, 2022 - Beale, Carter (Forestry Faculty, Universitas Hasanuddin, 2023)
In the Shadow of the Palms offers a haunting and novel perspective on themes of dispossession and alienation wrought by the expansion of oil palm agribusiness in Indonesia. Drawing on fieldwork with a Marind community in the Upper Bian in West Papua, the text endeavors to describe such dispossessory dynamics from an embodied Marind ontology. Meticulous descriptions of interactions with various animal and plant species evidence a profound intersubjectivity of human and environment in the Marind world. Moreover, these encounters with multi-species entanglements often reveal how the Marind accommodate and assimilate the spiritual and material incursions inflicted by expanding oil palm production. Chao's argument takes issue with recent theoretical trends in multispecies studies for their failure to engage